Psychological Features of Self-Realization in Chinese Women - S I Kudinov; I B Kudinova; - Zhang Teng (Peoples' Friendship University of Russia (RUDN University), 2013)
The article analyzes the results of the empirical study of self-realization of an individual. The study was performed on the Chinese respondents in the frame of the polysystemic concept of self-realization of the personality.